Karakter Morfologi Dan Anatomi Sawilangit (Vernonia Cinera L.) Pada Ketinggian Yang Berbeda - Sri Lestari; Dian Palupi; Riska Desi Aryani (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Vernonia cinerea L. (sawilangit) is a wild plant that has potential as a medicinal plant because of the secondary metabolites in each organ. This research aimed to explore the morphological and anatomical characters of the sawilangit that grow at different altitudes in Banyumas, Cilacap, and Purbalingga. Plant samples were taken using the purposive random sampling method at an altitude of <350 masl, 350–700 masl, and >700 masl. Sawilangit growing at <350 masl has superior morphological and anatomical characters than sawilangit growing at the other two altitudes, which have the characteristics of taller, wider leaf, larger stem diameters, and darker flower color. The observation on quantitative of morphological and anatomical characters showed that sawilangit at <350 masl has an average height of 66.17 cm, root diameter of 0.33 cm, stem diameter 0.32 cm, leaf length and width of 5.7 cm and 2.14 cm, and stomata index of 0.28. These results indicated that altitude <350 masl is suitable for sawilangit growth because it can produce optimal morphological and anatomical characteristics.